PENGARUH PERSELINGKUHAN DAN POLIGAMI DALAM KONFLIK KELUARGA: KAJIAN LITERATUR PSIKOLOGI KELUARGA ISLAM: Indonesia - Ahmad Supiannor; Taufik Hidayat (Makkah: Journal Of Islamic Studies, 2025)
This study explores the dynamics of family conflict triggered by the phenomena of infidelity and polygamy within the framework of Islamic family psychology. The objective of the research is to analyze the differences in psychological and sociological impacts between infidelity, viewed as a breach of commitment, and polygamy, which often triggers conflict due to structural unreadiness and emotional management issues. The method employed is a literature study (library research) with a qualitative-descriptive approach, analyzing various references related to family psychology and Islamic family law. The results indicate that infidelity leads to a profound breach of trust (betrayal trauma), while polygamy tends to trigger conflict due to unfair distribution of resources and attention, resulting in decreased psychological well-being for wives and children. The conclusion of this study emphasizes that although polygamy has legal standing, both phenomena have the potential to destroy family harmony if not managed with emotional maturity and the principle of justice. Conflict resolution in both phenomena requires a comprehensive psychological approach to restore the emotional stability of family members.